(untitled) (Journal of Namibian Studies : History Politics Culture, 2021)
In the top competitive Fast-Moving Consumer Goods (FMCG) industry, strategic performance measurement is essential for aligning organizational objectives with operational execution. This paper presents a conceptual framework for utilizing the Balanced Scorecard (BSC) as a multidimensional approach to strategic performance measurement in the FMCG sector. The BSC framework integrates financial and non-financial metrics across four key perspectives: financial, customer, internal business processes, and learning and growth. By doing so, it offers a comprehensive tool for organizations to monitor and manage performance in a way that supports long-term strategic goals. The conceptual framework developed in this paper emphasizes the need for a balanced approach, where traditional financial indicators are supplemented by metrics that reflect customer satisfaction, process efficiency, and organizational innovation. It also explores how the BSC can be tailored to the unique challenges and dynamics of the FMCG sector, such as rapid market changes and consumer behaviour shifts. This framework serves as a guide for FMCG companies aiming to enhance their strategic alignment, improve decision-making, and achieve sustainable growth. By adopting the BSC, organizations can achieve a more integrated and strategic approach to performance measurement, ultimately leading to better business outcomes in the competitive FMCG landscape.